Weight Gain Maternal In The Second Half Of Pregnancy Influencing The Fetal Macrosomia Pregestational Regardless Of Weight - Limay-Ríos, Oscar Antonio (2016)
Objectives. To determine the relationship between obesity at the beginning, in the second and third trimester of pregnancy and macrosomic newborns treated at the National Maternal Perinatal Institute during the period from 2003 to 2005. Materials and methods. An analytical, prospective study in which it was followed two cohorts of pregnant women, the first one with 210 pregnant with adequate prepregnancy weight or overweight; and the second one with 211 pregnant with prepregnancy maternal obesity. We proceeded to descriptive analysis, through percentages, means and standard deviations. For the determination of hypothesis tests proceeded to significant inferential statistics with an alpha level of statistical significance of less than 0.05. To determine the influence, it proceeded to use the Relative Risk (RR) with confidence intervals at 95%.